Indigenous Knowledge of the Edible Weaver Ant Oecophylla smaragdina Fabricius Hymenoptera: Formicidae from the Vientiane Plain, Lao PDR - Van Itterbeeck, Joost; Sivongxay, Niane; Praxaysombath, Bounthob; van Huis, Arnold (Ethnobiology Letters, 2014)
Of major importance in realizing the potential of edible insects as a core element in improving food security, sustainable food production, and biodiversity conservation, are developments in sustainable exploitation of wild edible insect populations and in (semi-)cultivating and farming edible insects. Such developments can draw on both western science and indigenous knowledge. Oecophylla smaragdina Fabricius Hymenoptera: Formicidae, of which particularly the queen brood is commonly consumed in Thailand and the Lao PDR, is believed to have the potential to act as flagship/umbrella species in forest conservation and management, to be incorporated simultaneously as biological control agent and direct source of human food in agroforestry practices, and to be (semi-)cultivated. We provide a detailed account of indigenous knowledge of O. smaragdina and ant brood collection practices from the Vientiane Plain, Lao PDR, through focus group discussions and participant observations, and then reflect on sustainability and conservation issues, and on semi-cultivating constraints and possibilities embedded in indigenous knowledge and ant brood collection practices.